2008
DOI: 10.1111/j.1365-2133.2008.08670.x
|View full text |Cite
|
Sign up to set email alerts
|

Pseudoclonality in cutaneous pseudolymphomas: a pitfall in interpretation of rearrangement studies

Abstract: B-cell and T-cell pseudoclones are not uncommonly encountered in moderately dense pseudolymphomatous infiltrates (23% and 13%, respectively). B-cell clonality is seen occasionally in pseudolymphomatous infiltrates (13%), especially when they are sparse in B lymphocytes. Therefore, rearrangement studies cannot be interpreted without correlation with morphological patterns and immunophenotyping of infiltrates and they need to be confirmed by duplicate or triplicate tests in order to prevent overinterpretation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
48
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 44 publications
3
48
1
Order By: Relevance
“…Pseudoclonality in cutaneous biopsies, which represented a majority of the samples in our study, is well documented in the literature with reported frequencies ranging from 0% to 24%. [33][34][35] We think that the mono-V assay could be susceptible to amplifying false-positive pseudoclonality since we detected a frequency of clonal TCR-␥ V11 GRs that is higher than that reported by others (studies 1, 3, 5, 6, 7, 8, 10; Table 5). We encountered several challenging clinical cases that support this observation.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Pseudoclonality in cutaneous biopsies, which represented a majority of the samples in our study, is well documented in the literature with reported frequencies ranging from 0% to 24%. [33][34][35] We think that the mono-V assay could be susceptible to amplifying false-positive pseudoclonality since we detected a frequency of clonal TCR-␥ V11 GRs that is higher than that reported by others (studies 1, 3, 5, 6, 7, 8, 10; Table 5). We encountered several challenging clinical cases that support this observation.…”
Section: Discussioncontrasting
confidence: 53%
“…Therefore, it is critical to avoid overcalling potential pseudoclonal results, which could occur because of a low number of lymphocytes in the sample, a pseudolymphoma of the skin, or an oligoclonal T-cell expansion in an inflammatory process. 22,33 We believe that the true frequency of clonal TCR-␥ V11 GRs is likely to be found somewhere in between the extremes listed in Table 5, 0% to 17%. However, a detailed analysis of J segment utilization and parallel testing under different PCR conditions is not feasible for routine clinical testing.…”
Section: Discussionmentioning
confidence: 99%
“…Immunoglobulin chain rearrangement showed a polyclonal process in 2 cases/2 and monoclonality in 1 case [5]. However, the appearance of this 36 × 13 mm plaque in the clinical plate provided in the report together with the histological pictures was very similar to that of the other cases of TLP and we feel that it belongs to this group, cutaneous marginal zone lymphoma being exceptional at this age [6,7,8,9], whereas clonal T- or B-cell populations have been encountered in clearly benign conditions and cannot be considered to be synonymous with malignancy [10]. …”
Section: Discussionmentioning
confidence: 93%
“…In contrast, the kappa light chain gene rearrangement was polyclonal. Several studies have demonstrated that clonal B cell populations can be identified in different lymphoid and nonlymphoid tissues involved by antigen-driven proliferations of B cells associated with pathogens, such as HIV [5], hepatitis C virus [10], Borrelia burgdorferi [11], herpes virus [12], Epstein-Barr virus, Cytomegalovirus, and Tropheryma whippelii [13]. In addition, [5].…”
Section: Discussionmentioning
confidence: 99%